Caring for resettled refugee children in the United States: guidelines, challenges and public health perspectives - Phung, Binh (Frontiers in Public Health, 2023)
The global refugee crisis has become an urgent, pressing humanitarian issue, with an estimated 37 million children forcibly displaced from their homes due to conflict, persecution, violence and other human rights violations by mid-2022. Of these children, only a small percentage are eligible for resettlement in a new country. This narrative review examines the physical health needs of resettled refugee children (RRC) in the United States. By analyzing nutrition and growth, infectious diseases, and general health care/screening measures, a set of comprehensive, evidence-based guidelines and public health perspectives are formulated to facilitate ongoing discussion to ensure that RRC receive equitable health care access. An urgent call to action emphasizes cross-border collaboration between governments, public health experts, refugee populations, and disease preparedness authorities in order to prioritize the physical health of RRC. This review will provide primary care providers, public health professionals, social service workers, and community advocates with up-to-date recommendations to meet the health needs of RRC in the U.S.